Optimasi Spesiasi Kromium Ke Bentuk Cr(III) - Tanat - Jenifer Alfonda Walewangko; Djefry Tani; Joice Caroles (Jurnal Kimia Fullerene, 2020)
This research was conducted to determine the heavy metal species of Cr (III). Determination of heavy metals is determined based on the required chromium species using the UV-Vis spectrophotometry method. The sample used was CrCl3.H2O and the complexing agent was tannic acid. This research was conducted to determine the effect of pH, concentration and time of stability by finding the optimum conditions of the chromium - tanic acid complex. The optimum pH is at pH 11, the optimum concentration is at a ratio of 5: 1 concentration (Cr: tanic acid), the stability of time is at the 10th minute.